An In-Depth Review of Organic Waste Treatment Using Black Soldier Fly (BFL) - Irfana Kabir Ahmad; Nur Fardilla Amrul; Noor Ezlin Ahmad Basri; Fatihah Suja; Nurul Ain Abdul Jalil; Nur Asyiqin Azman (Contemporary Research and Perspectives in Biological Science Vol. 8, 2025)
Population growth brings a higher standard of living that results in direct or indirect solid waste generation. Solid wastes are generated by the agricultural, commercial, construction, hazardous, industrial, and food sectors. The increase in solid waste generation is caused primarily by the global population growth that resulted in urban sprawl, economic development, and consumerism. Poor waste management has adverse impacts on the environment and human health. The recent years have seen increasing interest in using black soldier fly (BSF), Hermetia illucens, as an organic waste converter. Black soldier fly larvae (BSFL) feed voraciously on various types of organic waste, including food wastes, agro-industrial by-products, and chicken and dairy manure, and reduce the initial weight of the organic waste by about 50% in a shorter period than conventional composting. The main components of the BSFL system are the larvero, where the larvae feed and grow, and the fly house, where the adults BSF live and reproduce. It is essential to have a rearing facility that maintains healthy adult and larval BSF to provide a sufficient and continuous supply of offspring for organic waste treatment. The BSF organic waste processing facility consists of waste pre-processing, BSFL biowaste treatment, the separation of BSFL from the process residue, and larvae and residue refinement into marketable products. BSFL digest the nutrients in the wastes and convert them into beneficial proteins and fats used to produce animal feed, and BSFL residue can be used as an organic fertilizer. The study concluded that the two main by-products from the BSFL waste treatment system are the larvae and prepupae, which can be used as animal feed, while the residue can be used as organic fertilizer. Generally, the BSF organic waste treatment system is a green technology that reduces organic waste, even if the reduction is on a small scale. This review summarizes the BSFL treatment process to provide an in-depth understanding of the value of its by-products as animal feed and organic fertilizer.